Role of hydrocortisone in prevention of pain on propofol injection - Monu Yadav; Padmaja Durga; R Gopinath (Wolters Kluwer Medknow Publications, 2011)
Background and Objectives : Pain following intravenous injection of propofol continues to be an intriguing problem. None of the commonly used methods completely attenuate the pain. Inflammatory response to propofol contributes to the pain. Role of hydrocortisone in attenuating pain has not been evaluated. This study was conducted to compare the efficacy of lignocaine and hydrocortisone in attenuation of pain following intravenous injection of propofol. Materials and Methods : A prospective randomized double-blind, placebo-controlled study was conducted on 72 adult patients belonging to American Society of Anesthesiologists (ASA) physical status I or II, scheduled to undergo elective surgery. They were randomly assigned to four groups of 18 each. Group NS, group LG, group HC10, and group HC25. The groups received 2 ml normal saline, 2 ml 2% lignocaine, 10 mg/2 ml hydrocortisone, and 25 mg/2 ml hydrocortisone, respectively, as pretreatment. Propofol was injected 30 sec later. A blinded researcher assessed the patient's pain level using a four point verbal rating scale. Results : The four groups were comparable in respect to patient's characteristics. There was no significant difference of hemodynamics changes during propofol induction between all the groups. There was no statistically significant difference in the incidence of pain between patients who received hydrocortisone and the placebo group. The incidence of pain was significantly less in group LG than other three groups. Conclusion : Use of intravenous low dose hydrocortisone pretreatment of the vein does not attenuate pain following propofol injection.